Evaluation of antioxidant activities, toxicity studies and the DNA damage protective effect of various solvent extracts of Litsea cubeba fruits - Tapan Seal; Kausik Chaudhuri; Basundhara Pillai; Shrabana Chakrabarti; Tanmoy Mondal; Biswajit Auddy (Heliyon, 2020)
Litsea cubeba is devoured by the ethnic individuals of Arunachal Pradesh in India as food and has been traditionally used for curing different ailments. The purpose of present study was to investigate the antioxidant activities of fruits of L. cubeba using different solvent extracts, quantification of phenolics, toxicity studies and DNA damage protective activities. The antioxidant activities of fruits using five different solvent extracts completed utilizing different in vitro examines. The quantitation of phenolic and polyphenolic compounds in the methanol extract of the fruits was carried out by HPLC. The in vitro haemolytic examination of plant concentrates were completed on rat erythrocytes. Appraisal of cytotoxicity of eatable fruits was assessed by MTT measure. The genotoxicity of the contemplated plant was tried by the single-cell gel electrophoresis comet measure. The DNA defensive impacts of the aqueous extracts of fruits on rodent lymphocyte DNA lesions were likewise assessed with the comet test. The extract obtained by methanol exhibited the highest antioxidant activity. The HPLC examination of the methanol concentrate of the plant demonstrated the occurrence of different phenolic acids and flavonoids like caffeic acid (145.96μg/100mg DE), syringic acid (125.85 μg/100mg DE), ferulic acid (155.89 μg/100mg DE), apigenin (28.43 μg/100mg DE), kaempferol (53.41 μg/100mg DE) etc. in various amounts. The consequences of haemolytic lethality, cytotoxicity and genotoxicity of fluid concentrates of the edible plant ensure the security at cell and genomic level. The fluid concentrate of the plant fundamentally repressed DNA harm and these information recommend that the watery concentrate of L. cubeba can forestall oxidative DNA harm to rodent lymphocytes, which is likely because of antioxidant constituents in the concentrate. These outcomes demonstrate that L. cubeba can be utilized in dietary applications with a possibility to diminish oxidative pressure.